The problem of choosing the type of silo and the method of its construction in Ukraine - Chertkov, O.; Yermolovych, D. (Ways to Improve Construction Efficiency, 2018)
The article deals with the concept of silage, the classification of containers for the storage of grain crops. Various methods for constructing metal silos are described, their advantages and disadvantages are given. The author concluded that the landowners, who plan to store grain at the site of its collection, use a spiral-wound silo.